2013
DOI: 10.1155/2013/935675
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitane Triterpenoid fromMomordica charantiaInduces Apoptosis and Autophagy in Breast Cancer Cells, in Part, through Peroxisome Proliferator-Activated ReceptorγActivation

Abstract: Although the antitumor activity of the crude extract of wild bitter gourd (Momordica charantia L.) has been reported, its bioactive constituents and the underlying mechanism remain undefined. Here, we report that 3β,7β-dihydroxy-25-methoxycucurbita-5,23-diene-19-al (DMC), a cucurbitane-type triterpene isolated from wild bitter gourd, induced apoptotic death in breast cancer cells through peroxisome proliferator-activated receptor (PPAR) γ activation. Luciferase reporter assays indicated the ability of DMC to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Others have shown that a triterpenoid from wild gourd can elicit metabolic changes leading to autophagy and apoptosis in MCF7 cells via PPARc activation [36]. While PPARc is upstream of many of the effectors that are influenced by BAR, the PPARc agonist rosiglitazone did not recapitulate the effects of BAR on gene expression or prevent loss of metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that a triterpenoid from wild gourd can elicit metabolic changes leading to autophagy and apoptosis in MCF7 cells via PPARc activation [36]. While PPARc is upstream of many of the effectors that are influenced by BAR, the PPARc agonist rosiglitazone did not recapitulate the effects of BAR on gene expression or prevent loss of metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The cucurbitane-type triterpenoids were reported for several medicinal properties such as hypoglycemic, antiproliferative activities and also used for the treatment of free radical and reactive oxygen species mediated diseases [30]. In addition, these compounds were reported as partial agonist/antagonist for estrogen receptors such as ER␣ and ER␤ and were used for the management of estrogen related health problems [44]. Some of the newly identified triterpenoids with their structure are shown in Fig.…”
Section: Cucurbitane Type Triterpenoidsmentioning
confidence: 99%
“…Manoharan et al [63] described the mechanisms of this phytochemical in different cancer cell lines, ␣-momorcharin and ␤-momorcharin increased the cell death specifically in cancer cell lines by increasing the caspase-3 and 9 activities, releasing cytochrome c and elevating calcium level. Recently, Weng et al [44] isolated a novel cucurbitane-type triterpenoid (3β, 7β-dihydroxy-25-methoxycucurbita-5, 23-diene-19-al) from wild bitter gourd that induces apoptotic death in breast cancer cells. Ramalhete et al [64] proved that some novel cucurbitacins, balsaminagenin B, balsaminoside A and the known cucurbitacin karavelagenin C, together with some new mono or diacylated derivatives of karavelagenin C from aerial parts of M. balsamina strongly inhibited the human MDR1 gene transfected to mouse lymphoma cells.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Mutations, amplification and overexpression of this protein, which alters cell cycle progression, are frequently observed in a variety of tumors and may contribute to tumorigenesis. Cyclin D1 has been reported to be involved in tumorigenesis in breast cancer (67), prostate cancer (68), colorectal cancer (59,69), ovarian carcinoma (70), non-small cell lung cancer (71) and gastric carcinoma (72) cells.…”
Section: Mitogen-activated Protein Kinase (Mapk) Signaling Pathwaymentioning
confidence: 99%